Cytosolic herpes simplex virus capsids not only require binding inner tegument protein pUL36 but also pUL37 for active transport prior to secondary envelopment. (20th December 2012) - Sandbaumhüter, Malte; Döhner, Katinka; Schipke, Julia; Binz, Anne; Pohlmann, Anja; Sodeik, Beate; Bauerfeind, Rudolf
Summary As the inner tegument proteins pUL36 and pUL37 of alphaherpesviruses may contribute to efficient intracellular transport of viral particles, we investigated their role in cytosolic capsid motility during assembly of herpes simplex virus type 1 (HSV1). As reported previously for pUL36, untagged pUL37 and UL37GFP bound to cytosolic capsids before these acquired outer tegument and envelope proteins. Capsids tagged with CheVP26 analysed by live cell imaging were capable of directed long‐distance cytoplasmic transport during the assembly of wild‐type virions, while capsids of the HSV1‐ΔUL37 or HSV1‐ΔUL36 deletion mutants showed only random, undirected motion. The HSV1‐ΔUL37 phenotype was restored when UL37GFP had been overexpressed prior to infection. Quantitative immunoelectron microscopy revealed that capsids of HSV1‐ΔUL37 still recruited pUL36, whereas pUL37 did not colocalize with capsids of HSV1‐ΔUL36. Nevertheless, the cytosolic capsids of neither mutant could undergo secondary envelopment. Our data suggest that pUL36 and pUL37 are important prior to their functions in linking the inner to the outer tegument. Efficient capsid transport to the organelle of secondary envelopment requires recruitment ofpUL37 onto capsids, most likely via its interaction with pUL36, while capsid‐associated pUL36 alone is insufficient.